Genre Analysis of Online Private Class During the COVID-19 Pandemic - Agustina, Annisa; Cahyono, Setyo Prasiyanto (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2022)
The study aims to describe the social functions, linguistic features, and schematic structures in order to understand how the genre applies in online private class among teacher and student. This study used the qualitative method to analyze the data. The researchers collected the data from the video recording of the online private class that contain of a lecturer and the student. The researcher asked the data from the lecturer itself. Meanwhile, in analyzing the data the researchers employs a theory of genre analysis proposed by Gerot and Wignell (1995) to get the social functions, linguistic features, and schematic structures of the whole interactions. Furthermore, the result of this study indicates that the social functions of the interaction is to give students information about the material of the writing the English text, then, the schematic structures in the interactions of online private class is, as follows: greetings^opening conversations^bringing the topic^pre closing^leave taking. In addition, the linguistics features of the interaction is indicated by the use of simple present tense such as the use of is, do, does, and some modalities such as will, can, and may.